Current developments of RILEM TC 254-CMS ‘Thermal Cracking of Massive Concrete Structures’ - Fairbairn, Eduardo (2017)
This paper deals with an in-depth explanation about management and scientific aspects of RILEM Technical Committee 254-CMS μThermal Cracking of Massive Concrete Structures’. This RILEM TC has been set up in 2013 and has met 11 times since its creation. Up to this stage, the focus of the TC has been centered in the preparation of a state-of-the-art report, whose structure is described in detail in the paper. Further information is also given in regard to the management structure of the TC, as well as operational matters related to meetings (both online and actual meetings) and the collaborative environment setup in Google Drive and DROPBO; for the operation of the TC